Visual Dignity in Art - Dorot, Ruth (Journal of Education Culture and Society, 2020)
Aim. The aim of this article is to deal with visual dignity in the field of western art throughout the ages as it seeks to present the artistic and design devices employed by artists in order to compose and convey this aura of dignity. Moreover, it addresses the ways in which they create various kinds of atmosphere of respect and dignity felt by the observer regarding the topic and object of the painting or sculpture. Methods. In order to achieve this aim, the article examines seven masterpieces which explore the visual representations of various perceptions of dignity and their implications. Among the elements affecting the creation of dignity in the visual domain one finds: an impressive or majestic appearance, noblesse, self-esteem, pride, self-confidence, inner strength, authoritativeness and charisma. At times, the respectful treatment of the figures is clear as soon as one views the work, but at others it is implied in the interpretation given to it. It is not this article’s intention to discuss the different perceptions or expressions of human dignity, historically, theologically, politically, psychologically, nationally or socially, but to present them artistically as they are the innate right of people to be appreciated, treated with courtesy and met with ethical behavior. Results and conclusion. The research done in order to reach a conclusion confirming or contradicting the premises at its base, resulted in a mosaic of situations in which human dignity is reflected. The range of possibilities at the artists’ disposal for creating this value is diverse and includes: composition, use of color, mimesis, embellishment, disfigurement or distortion of reality. The pieces examined present: a military commander at the moment of his foe’s surrender; an author monumentally impressive, man of vision and power and of grand dimensions, rising up from a stone plinth; a stern-faced, disfigured dwarf considered a ‘curiosity’, seated on the ground; a family of farmers living an impoverished and meager life; and a Jesus-like mysterious intellectual and Moses the prophet. All these together at first glance appear to be a strange collection of works, in which the common denominator is unclear or seemingly absent. However, this diverse group is included in the article because of the aura of dignity the figures command or convey. At times, the respectful treatment of the figures is clear as soon as one views the work, but at others it is implied in the interpretation given to it.